2009
DOI: 10.1055/s-0029-1185766
|View full text |Cite
|
Sign up to set email alerts
|

Intraaortic Balloon Pumping in Patients with Right Ventricular Insufficiency after Cardiac Surgery: Parameters to Predict Failure of IABP Support

Abstract: In patients with IABP support for postcardiotomy cardiogenic shock, elevated serum lactate, elevated base deficit, hypotension, oliguria and large vasopressor doses are all predictors of mortality. In these patients, the use of another mechanical assist device should be considered in good time. Our study additionally shows that LCOS caused by predominantly right ventricular failure - particularly after CABG - may be an additional indication for IABP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 23 publications
0
17
0
3
Order By: Relevance
“…Intra-aortic balloon pumps improved RV function in sheep where RV failure was induced by increasing RV afterload [113]. Intra-aortic balloon counterpulsation in low output syndromes due to RV failure resulted in increased cardiac output and decreased wedge pressure [114][115][116]. However, a later study demonstrated improvement in cardiac output but no improvement in RVEF or LVEF [116].…”
Section: \6mentioning
confidence: 94%
“…Intra-aortic balloon pumps improved RV function in sheep where RV failure was induced by increasing RV afterload [113]. Intra-aortic balloon counterpulsation in low output syndromes due to RV failure resulted in increased cardiac output and decreased wedge pressure [114][115][116]. However, a later study demonstrated improvement in cardiac output but no improvement in RVEF or LVEF [116].…”
Section: \6mentioning
confidence: 94%
“…Hypotension and/or shock following CABG surgery can be attributed to the significant decrease in postoperative RV function . Our previous study also demonstrated that patients with preoperative decreased RV function tended to experience hypotension and/or shock in the early stages after CABG surgery.…”
Section: Discussionmentioning
confidence: 80%
“…The indication in this case is subject to important controversy, 84,85 though there are experiences that report an increase in CI and mean blood pressure (MBP) within one hour after insertion, and with a high disconnection (75%) and hospital survival rate (69%). This benefit has been related to the diastolic increase in blood flow to the right coronary artery, which may improve ventricle function, and to the reduction in systemic vascular resistance which can indirectly increase the contractile capacity of the right ventricle.…”
Section: In the Case Of Predominant Right Ventricle Failure: Is An Inmentioning
confidence: 94%
“…There are a series of useful prognostic scales or clinical and biochemical markers allowing us to predict the success or failure of IABP on an early basis. In this sense, Boeken et al 84 When is an intraaortic counterpulsation balloon pump contraindicated in the heart surgery patient?…”
Section: In the Case Of Predominant Right Ventricle Failure: Is An Inmentioning
confidence: 98%